The BLUE model (Branding, leisure, and unique experience) for Improving mangrove tourism destination branding in East Java - Budiarti, Endah; Andjarwati, Tri; Gunawan, Kunto Inggit (Edelweiss Applied Science and Technology, 2024)
This study aims to develop BLUE (Branding, Leisure, and Unique Experience) model as a strategic approach to improve destination branding for mangrove tourism in East Java. As competition among tourist destinations intensifies, developing branding concepts on experiential and recreational activities has become key to attracting visitors and differentiating destinations from competitors. This research utilizes both qualitative and quantitative methods, including in-depth interviews with local stakeholders and surveys of tourists. The findings reveal that the BLUE concept provides a comprehensive framework for managing nature-based tourism destinations while maintaining a balance between natural attractions, unique visitor experiences, and environmental conservation. This model is expected to enhance the competitiveness of East Java’s mangrove tourism in both domestic and international markets.